Effect of the acid degradation on the properties of polyester reinforced with glass fibers (2010)
The current article focuses on evaluating the effect of the half acid degradation in the mechanical and other properties and in the structural integrity of a polyester fiber-reinforced glass in two different orientation types:Mat, in taffeta and multiaxial fabrics, after the immersion process in nitric acid to 5 % of volume.